Tepung Tapioka, Kentang, dan Jagung sebagai Purifikasi Minyak Goreng Bekas (Kajian Kadar Malondealdehid, Asam Lemak Bebas, dan Tingkat Kekeruhan): Tapioca, Potato, and Corn Starch as Purifying Agent of Used Cooking Oil (Study Of Malondialdehyde, Free Fatty Acids and Turbidity Levels) - Susilo, Jatmiko; Siswanta Jaka Purnama; Salsabiela Dwiyudrisa Suyudi (Indonesian Journal of Pharmacy and Natural Product, 2023)
Consumption of repeating heated cooking oil, and its fumes cause a high incidence of genotoxic, mutagenic, tumorogenic, and various types of cancer. Amylose affects oil absorption by interfering with the structural evolution of starch or by interacting directly with lipids during frying. This study aimed to analyze the effect of tapioca, potato, and corn flour on improving the quality of used cooking oil by studying malondialdehyde (MDA) levels. Free fatty acids (ALB) and turbidity levels. Experimental research with pre-test and post-test designs, using tapioca, potatoes and corn fluor (5; 10 and 20 g) as purifiers in 100 ml of used cooking oil. Flour frying is carried out at a temperature of 160-165 °C for 5 minutes. MDA levels were determined using the spectrophotometric TBARs method at λmax: 532 nm, alkalimetry to determine ALB levels, while the turbidity level was spectrophotometric at λmax: 448 nm with comparison to fresh cooking oil. The three types of flour were able to reduce levels of MDA, ALB, and turbidity (p<0.001). The type of flour decreased (p>0.5), while the amount of flour decreased MDA and turbidity levels (p<0.0001), but ALB levels (p>0.5). This research has proven that flour (tapioca, wheat and corn) can improve the quality of used cooking oil by reducing MDA, ALB and turbidity levels. ABSTRAK Konsumsi minyak goreng yang dipanaskan berulang kali dan asapnya menyebabkan tingginya insiden genotoksik, mutagenik, tumorogenik, dan berbagai jenis kanker. Amilosa mempengaruhi penyerapan minyak dengan mengganggu evolusi struktural amilum atau dengan berinteraksi langsung dengan lipid selama penggorengan Penelitian bertujuan untuk menganalisis pengaruh tepung tapioka, kentang, dan jagung terhadap peningkatan kualitas minyak bekas goreng dengan kajian kadar malondealdehid (MDA). Asam lemak bebas (ALB) dan tingkat kekeruhan. Penelitian eksperimental dengan desain pre-test dan post-test, menggunakan tepung tapioka, kentang dan jagung (5 ; 10 dan 20 g) sebagai pemurni dalam 100 ml minyak bekas goreng. Penggorengan tepung dilakukan pada suhu 160-165 °C selama 5 menit. Kadar MDA ditetapkan menggunakan metoda TBARs spektroforometri pada λmaks:532 nm, alkalimetri untuk menetapkan kadar ALB, sedangkan tingkat kekeruhan dengan spektrofotometri pada λmaks:448 nm dengan pembanding minyak goreng baru. Hasil penelitian ini adalah ketiga jenis tepung mampu menurunkan kadar MDA, ALB, dan kekeruhan (p<0,001). Jenis tepung mengalami penurunan (p>0,5), sedangkan jumlah tepung mengalami penurunan kadar MDA dan kekeruhan (p<0,0001), tetapi kadar ALB (p>0,5). Penelitian ini telah membuktikan tepung (tapioka, terigu, dan jagung) mampu meningkatkan kualitas minyak goreng bekas dengan menurunkan kadar MDA, ALB dan tingkat kekeruhan.